Faith, unity, discipline : the Inter-Service-Intelligence (ISI) of Pakistan - Kiessling, Hein G. (Hein Günter) (C. Hurst & Company, 2016)
Established in the wake of the Indo-Pakistani War of 1947-8 by British officer Major General Robert Cawthorne, then Deputy Chief of Staff in the Pakistan Army, Pakistan's Inter-Services Intelligence (ISI) for years remained an under-developed and obscure agency. In 1979, the organisation's growing importance was felt during the Soviet war in Afghanistan, as it worked hand in glove with the CIA to support the mujahideen resistance, but its activities received little coverage in news media. Since that time, the ISI has projected its influence across the region in 1988 its involvement in Indian.